Awareness of Accountability, Mutual Cooperation, and Honesty in the Application of Accounting - Sepfriani, Intan; Gafur, Abdul (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to find awareness of responsibility, mutual cooperation, and honesty in the Nuha Collection in its recording. Qualitative research is used with the type of phenomenological research, then the subject in this study is the Owner Nuha Collection, Nuha Collection employees in the Production, Cashier, and Admin sections, and the data collection techniques used are interviews and observation. The results of this study indicate that accountability in Nuha prioritizes consumer rights. Mutual cooperation is also seen with the same energy to produce products according to orders. However, honesty here has not run optimally